Vegetation composition and structure changes following roller-chopping deforestation in central Argentina woodlands - Steinaker, Diego F.; Jobbagy Gampel, Esteban Gabriel; Martini, Juan Pablo; Arroyo, Daniel Nicolas; Pacheco, Jorge L.; Marchesini, Victoria A. (2018)
Driven by the pressure of increasing forage production, dry forests and woodlands of Argentina are suffering one of the highest deforestation rates in the world. In this study we combined field work and a remote sensing approach to assess the successional trajectory in terms of functional group diversity and ecosystem phenology, following roller chopping deforestation in a woodland of central Argentina. The first year after disturbance, shrub cover decreased at the same proportion than grass cover increased while tree cover was drastically reduced. After 3 years, shrubs recovered 70% of the original cover and grasses maintained a relatively high proportion, but tree cover remained low. Roller-chopping favoured early over late successional species in the case of woody plants, but had the inverse effect in the case of grasses. At ecosystem scale the length of the growing season was drastically shortened by 100 days following disturbance. Roller chopping improves ecosystem services of provision by enhancing forage’s offer but at the same time deteriorated the system by reducing functional plant diversity and by shortening the growing season, with potential cascade-consequences on other ecosystem processes such as the carbon and water dynamics.